The future of ocean governance and capacity development: essays in honor of Elisabeth Mann Borgese (1918-2002) - Werle, Dirk (Brill Nijhoff, 2018)
The International Ocean Institute - Canada has compiled over 80 insightful essays on the future of ocean governance and capacity development. The book honors the work of Elisabeth Mann Borgese (1918-2002), preeminent ocean advocate and founder of the IOI.0More than 90 leading experts explore future challenges and opportunities for ocean governance and capacity development. Major themes include the law of the sea, ocean sciences, integrated coastal and ocean management, fisheries and aquaculture, communication and negotiations, maritime safety and security, ocean energy, and maritime transportation. These themes parallel those covered in the Institute's annual Training Program at Dalhousie University in Canada. The essay collection is aimed at professionals, students and citizens alike